VARIASI KONSENTRASI EKSTRAK DAUN ASHITABA (Angelica keiskei) TERHADAP PERTUMBUHAN BAKTERI Staphyloccus aureus - Risa Umami (Bioscientist : Jurnal Ilmiah Biologi, 2017)
Abstract : Acne is a common skin disease that begins with increased sebum production and is aggravated by the presence of bacterial attacks. Ashitaba (Angelica keiskei) leaf extract Introduced has antibacterial activity against Staphylococcus aureus acne bacteria. The purpose of this study was to assess the antibacterial power of Ashitaba  (Angelica keiskei) leaf extract to the growth of Staphylococcus aureus. The treatment in this study used six treatments consisting of five treatments with the concentration of Ashitaba leaf extract  (5%, 10%, 25%, 50%, and 100%) while one treatment was positive control using tetracycline. The results showed that the inhibitory zone diameter was formed at concentrations of 25% to 100% with the largest diameter being 100%. This gives rise to higher concentrations, the higher the active compounds are Ashitaba leaf extract. Others with positive controls indicate a small inhibitory zone diameter as Staphylococcus aureus bacteria have been resistance with this antibiotic due to long-term use.